Quantitative Characteristics of Crossing Bali Cows with Different Strain of Bulls in Waelata District Buru Regency - Umaternate, Shahrun M.; Rajab, Rajab; Papilaya, Bercomien J. (Universitas Jember, 2023)
This study aims to determine the quantitative characteristics of the crossbreed Bali cattle with several male breeds such as the Ongole, Limousine, and Simmental breeds. The method used in this research is the observation method in the form of direct observation in the field and measurement of cattle. A total of 30 adult cattle aged 1.5-2 years, consisting of 10 heads each (5 males and 5 females) crosses through Artificial Insemination (AI) of Bali cattle using frozen semen of Ongole breed bulls (POBAL), Limousin (LIMBAL) and Simmental (SIMBAL). The results showed that POBAL cattle had an average body length of 114.4-116.0 cm, chest circumference 179.4-220.0 cm, shoulder height 126.2-143.8 cm, and body weight 407.15-586.84 kg . LIMBAL cattle have an average body length ranging from 129.4-151.2 cm, chest circumference 170.4-191.8 cm, shoulder height 123.0-151.6 cm, and body weight 370.184-457.122 kg. While the average body length for SIMBAL cattle ranges from 159.8-180.0 cm, chest circumference 166.6-219.8 cm, shoulder height 125.8-154.1 cm, and body weight 356.662-584.678 kg.